Synthesis of Patchouli Biochar Cr2O3 Composite Using Double Acid Oxidators for Paracetamol Adsorption - Tutik Setianingsih; Masruri Masruri; Bambang Ismuyanto (The Journal of Pure and Applied Chemistry Research, 2018)
Composite built by patchouli biochar and metal oxide, Cr2O3, is a potential material for remediation of contaminated wasterwater. Oxidation of biochar using acid or salt oxidators can improve its surface polar functional groups. This treatment may be able to increase impregnation of  metal cation (as salt) before calcination to form its oxide. In this research, 3 types of oxidators were used to oxidize the biochar before impregnation with purpose to study its influence toward physichochemistry and adsorption performance of the composite. Preparation of the composite included 3 steps, including preparation of biochar by pyrolisis of patchouli biomass using ZnCl2 activator at 450 oC, oxidation of the biochar using 3 different oxidators (H2SO4-HNO3, H3PO4-HNO3, H2O2–HNO3) at 60 oC,  impregnation of the oxidized biochar using CrCl3 followed by calcination process to form biochar–Cr2O3 composite at 600 oC. Characterization using X-ray diffraction indicated that the composite containes the Cr2O3 structure.  FTIR spectrophotometry characterization indicates the different content of C=O, C-O, and –OH on the composite surface. SEM images shows irregular micro ball shapes. EDX characterization indicates the different Cr content in the composite with same sequence with FTIR absorbances of  both C-O and –OH. Adsorption of paracetamol  indicates effect of Cr2O3 showing the same sequence of both.